The Evans–Tishchenko Reaction: Scope and Applications - Ralston, Kevin J.; Hulme, Alison N. (Synthesis, 2012)
The Evans–Tishchenko reaction provides a highly diastereoselective route towards the synthesis of 1,3-anti diol monoesters, and therefore has found prominent use in a number of synthetic applications. This review summarises recent applications of the Evans–Tishchenko reaction in natural product synthesis, and examines scope in terms of substrate range, functional group tolerance, and catalyst.1 Introduction2 Reaction Mechanism and Catalyst Scope2.1 Reaction Mechanism2.2 Samarium2.3 Scandium2.4 Zirconium2.5 Other Metals3 Substrate Scope4 Application in Natural Product Synthesis4.1 Protection/Asymmetric Induction4.2 Functional Group Interconversion4.3 Fragment Linkage and Ring Formation5 Future Perspectives6 Conclusion
Keywords: Evans–Tishchenko reaction; anti-1,3-diols; diastereoselectivity; Lewis acids; samarium; natural products